Limiting Performance of Helmets for the Prevention of Head Injury. (1999) - Cheng, Z.Q.; Pilkey, W.D.; Crandall, J.R.; Bass, C.R.; Darvish, K.
Abstract : This is a study of the theoretical optimal (limiting) performance of helmets for the prevention of head injury. A rigid head injury model and a two-mass translational head injury model are employed. Several head injury criteria are utilized, including head acceleration, the head injury criterion (HIC), the energy imparted to the brain which is related to brain injury, and the power developed in the skull that is associated with skull fracture. A helmeted head hitting a rigid surface and a helmeted head hit by a moving object such as a ball are considered. The optimal characteristics of helmets and the impact responses of the helmeted head are investigated computationally. An experiment is conducted on an ensemble of bicycle helmets. Computational results are compared with the experimental results.